Rechenka's eggs - Polacco, Patricia (Philomel Books, 1988)
An injured goose rescued by Babushka, having broken the painted eggs intended for the Easter Festival in Moscva, lays thirteen marvelously colored eggs to replace them, then leaves behind one final miracle in egg form before returning to her own kind.